Biogenic Amines in Fish and Shellfish - Rawles, Dafne D.; Flick, George J.; Martin, Roy E. (Advances in Food and Nutrition Research, 1996)
This chapter focuses on biogenic amines in fish and shellfish. The term “biogenic amines” refers to the nonvolatile amines, such as cadaverine, putrescine, spermidine, spermine, tyramine, tryptamine, and histamine, produced post mortem in fish and shellfish products. The compounds are reported to originate from the decarboxylation of specific free amino acids in fish or shellfish tissue. Chemically, the biogenic amines are defined as low-molecular-weight aliphatic, alicyclic, or heterocyclic organic bases. The use of chemical compounds as objective product standards or the indices of quality has long been suggested because these tests are rapid when compared to traditional microbiological analyses and less subject to individual interpretation than sensory analyses. Moreover, clinical studies have considered the activity of diamine oxidases to be a useful parameter, thus, many different assays to determine the activity of diamine oxidases have been proposed. Procedures using radioactive substrate achieve high sensitivity and most recently the use of high-performance liquid chromatography has been described.